Hydrological (in)stability in Southern Siberia during the Younger Dryas and early Holocene - Harding, P; Bezrukova, EV; Kostrova, SS; Lacey, JH; Leng, MJ; Meyer, H; Pavlova, LA; Shchetnikov, A; Shtenberg, MV; Tarasov, PE; Mackay, AW (Elsevier BV, 2020)
Southern Siberia is currently undergoing rapid warming, inducing changes in vegetation, loss of permafrost, and impacts on the hydrodynamics of lakes and rivers. Lake sediments are key archives of environmental change and contain a record of ecosystem variability, as well as providing proxy indicators of wider environmental and climatic change. Investigating how hydrological systems have responded to past shifts in climate can provide essential context for better understanding future ecosystem changes in Siberia. Oxygen isotope ratios within lacustrine records provide fundamental information on past variability in hydrological systems. Here we present a new oxygen isotope record from diatom silica (ẟ18Odiatom) at Lake Baunt (55°11′15″N, 113°01,45″E), in the southern part of eastern Siberia, and consider how the site has responded to climate changes between the Younger Dryas and Early to Mid Holocene (ca. 12.4 to 6.2 ka cal BP). Excursions in ẟ18Odiatom are influenced by air temperature and the seasonality, quantity, and source of atmospheric precipitation. These variables are a function of the strength of the Siberian High, which controls temperature, the proportion and quantity of winter versus summer precipitation, and the relative dominance of Atlantic versus Pacific air masses. A regional comparison with other Siberian ẟ18Odiatom records, from lakes Baikal and Kotokel, suggests that ẟ18Odiatom variations in southern Siberia reflect increased continentality during the Younger Dryas, delayed Early Holocene warming in the region, and substantial climate instability between ~10.5 to ~8.2 ka cal BP. Unstable conditions during the Early Holocene thermal optimum most likely reflect localised changes from glacial melting. Taking the profiles from three very different lakes together, highlight the influence of site specific factors on the individual records, and how one site is not indicative of the region as a whole. Overall, the study documents how sensitive this important region is to both internal and external ...